2016
DOI: 10.1016/j.aninu.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary alfalfa flavonoids extraction on growth performance, organ development and blood biochemical indexes of Yangzhou geese aged from 28 to 70 days

Abstract: This experiment was conducted to study the effects of dietary alfalfa flavonoids extraction supplemental level on growth performance, organ development and blood biochemical indexes of Yangzhou geese at the age of 28 to 70 days. Two hundred and forty 21-day-old healthy male geese with similar body weight were randomly distributed into 4 groups with 6 replicates per group and 10 geese per replicate. Geese in the control group were fed a basal diet and the others in the experimental groups (groups 1, 2, and 3) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 2 publications
7
46
1
1
Order By: Relevance
“…These results are in agreement with those reported for Yang zhou geese by Chen et al [ 15 ] who did not find any significant difference for slaughter performance except for the breast muscle weight and ratio which were significantly higher than those in the control group.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with those reported for Yang zhou geese by Chen et al [ 15 ] who did not find any significant difference for slaughter performance except for the breast muscle weight and ratio which were significantly higher than those in the control group.…”
Section: Resultssupporting
confidence: 93%
“…Ouyang et al [ 29 ] reported that inclusion of AAF in broiler chickens could improve the growth performance when compared with the control group, especially when the inclusion level was 15 mg/kg diet. In the same context, Chen et al [ 15 ] showed that AAF adding in thediet with 300 mg/kg significantly increased feed intake, average daily gain and final weight of Yangzhou geese aged from 28 to 70 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the total flavonoids, consisted of flavone, flavone Cglycoside, and flavonol, present powerful antioxidant activities. Recent papers have reported that flavonoids isolated from alfalfa could improve DPPH free-radical-scavenging activity, antioxidant activity, and growth performance [21,36]. Antioxidants are a group of providing electrons or unpaired electrons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average daily gain and body weight of the broilers fed with flavonoids were higher than those of broilers fed with basal diet. Chen et al [21] reported that the average daily gain of Yangzhou geese fed with alfalfa flavonoids was significantly higher than that of the control group fed with basal diet and the blood biochemical indices could be increased. However, there have been currently few studies about the identification of alfalfa flavonoids and analysis of dominant in vitro antioxidant by DPPH ⋅ -UHPLC.…”
Section: Introductionmentioning
confidence: 99%